OTURARAK VOLEYBOL OYNAYAN ENGELLİ SPORCULARDA BENLİK SAYGISI - YANLIÇ, NİDA (Fırat Üniveristesi, 2011)
Sportif etkinliklere katılan bireyler oyun ve hareketler aracılığıyla duygularını ifade etme imkânı bulur aynı zamanda saldırganlık, utangaçlık, kıskançlık gibi duyguların boşalımını sağlayarak, fiziksel olduğu kadar sosyal gelişimlerine de katkıda bulunurlar. Bu çalışmanın amacı oturarak voleybol oynayan bedensel engelli sporcuların benlik saygısı düzeylerini araştırmaktır.Araştırmanın evrenini Oturarak Voleybol Türkiye Şampiyonası'na katılan 77 erkek, 5 kadın toplam 82 bedensel engelli sporcu oluşturmaktadır. Çalışmada evrenin tamamına ulaşıldığı için örneklem alınmamıştır. Araştırma tipi olarak tanımlayıcı model esas alınmıştır. Veri toplama aracı olarak; 8 soruluk ?Kişisel Bilgi Formu? ile S. Coopersmith tarafından geliştirilen 25 soruluk ?Benlik Saygısı Envanteri? kullanılmıştır. Çalışmadan elde edilen verilerin analizleri istatistik paket programıyla t testi, One Way ANOVA, yüzde ve frekans dağılımı şeklinde değerlendirilmiştir.Araştırma sonucunda oturarak voleybol oynayan bedensel engelli sporcuların benlik saygısı puanlarının ( :73,02) yüksek düzeyde olduğu saptandı. Cinsiyet, yaş, medeni durum, eğitim durumu, anne-baba eğitim durumu, aylık gelir ve engel gerekçesi açısından benlik saygısı puanları arasında anlamlı bir farklılık olmadığı görülürken (p>0,05), engel düzeyi açısından benlik saygısı puanları arasında anlamlı farklılık olduğu tespit edilmiştir (p<0,05).Sonuç olarak oturarak voleybol oynayan bedensel engelli sporcuların benlik saygısı düzeylerinin yüksek seviyede olduğu söylenebilir.Anahtar kelimeler: Bedensel Engelli, Oturarak Voleybol, Benlik Saygısı, Engelliler İçin Spor

Individuals who participate to the sportive activities find opportunity to Express their emotions through games and actions, and they, beside their physical development, also contribute to their social development by ensuring their feelings like aggression, shyness, jealousy be discharged as well. The purpose of these study is to survey the self-esteem level of the handicapped sportsmen who play sitting volleyball.The nature of the survey is consisted of 77 male, 5 female, totally 82 physically handicapped sportsmen who participated to the Sitting Volleyball Turkey Championship. No any samples have been taken, for the whole nature was obtained in the study. The descriptive model of study type was taken as a basis. ?Personal Information Form? consisted of 8 questions and ?Inventory of Self-esteem?, developed by S. Coopersmith, consisted of 25 questions were used as data collection tools. The data analyses obtained from the study have been assessed by statistical package program, by way of t test, One Way ANOVA, percent and frequency distribution.As the result of the survey, it was found that the self-esteem points ( :73,02) of the physically handicapped sportsmen who play sitting volleyball is of high level. While seeing that there is no any significant difference between the self-esteem points (p>0,05) in respect of gender, age, marital status, educational status, parent?s educational status, monthly income and the reason of the handicap, it was found that there was a significant difference between the self-esteem points with respect to the handicap level (p<0,05).As a conclusion it could be said that the self-esteem level of the physically handicapped sportsmen who play sitting volleyball, is high.Keywords: Physically Handicapped, Sitting Volleyball, Self-esteem, Sports for the disabled
Self-esteem of the disabled sitting volleyball players
Keywords: Spor